Influenza vaccination in children with cystic fibrosis. (April 2013) - Patria, Maria Francesca; Longhi, Benedetta; Esposito, Susanna
Cystic fibrosis (CF) is an inherited autosomal recessive disease characterized by progressive pulmonary damage and respiratory failure. It is known that bacterial infections play a critical role in the development of significant lung damage, whereas the role of respiratory viruses in CF pulmonary exacerbations and the relationship between viral infections and the progression of lung damage are uncertain. Health authorities throughout the world recommend influenza vaccination for CF patients. The aim of this review is to analyze the impact of seasonal and pandemic influenza on CF patients and data concerning influenza vaccination in order to assess the current situation and identify areas for future study. As data are limited, further well-constructed clinical studies of the effectiveness of influenza vaccination on the main clinical outcome measures of pulmonary function and nutritional status in patients with CF are required.